Designing an Instrument for Assessing Junior High School English Teachers’ TPACK in Jayapura Papua - Ince Rezky Naing; Rommy D.B. Rambet (Universitas Islam Negeri Palopo, 2025)
In the digital era, the expectation for teachers to use technology effectively as part of their pedagogy continues to rise. However, many English teachers, especially in Papua, face significant challenges due to limited digital infrastructure, lack of training, and minimal contextualized assessment tools. To date, no standardized or context-sensitive instrument has been available to measure the Technological Pedagogical Content Knowledge (TPACK) of junior high school English teachers in Papua, particularly in Jayapura. To address this gap, this study developed and validated an instrument in the form of a self-report questionnaire to measure English teachers’ Technological Pedagogical Content Knowledge (TPACK) at the junior high school level in Jayapura, Papua. Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model as a development framework, the questionnaire covered seven TPACK components and consisted of 28 context-based items. Expert validation and pilot testing with 34 teachers confirmed satisfactory construct validity (r > 0.30) and high reliability (Cronbach’s Alpha = 0.966). The Content Validity Index (CVI) of 0.92 indicated strong relevance and clarity. The findings confirm that the developed self-report questionnaire is valid, reliable, and well-suited to Papua’s educational context. It functions both as a measurement tool and as a means for teachers’ self-reflection, supporting future research and professional development initiatives